LINQ for dummies - Mueller, John, 1958- (--For dummies., 2008)
If you've asked yourself "Why can't I develop database and XML queries in a language I already know?", then Language INtegrated Query, or LINQ, is for you. LINQ For Dummies introduces you to LINQ and the .NET Framework technologies, so you can use LINQ to query any object, any data set, any kind of XML, and SQL Server--no questions asked. This plain-English guide gives you a thorough overview of LINQ, from understanding the tasks it performs to making LINQ work with both Visual Basic and Visual Studio 2005. It explains the four LINQ providers in the .NET Framework, the easiest ways to go about a